Perceptions towards electronic cigarettes for smoking cessation among Stop Smoking Service users. Issue 2 (16th December 2015) - Sherratt, Frances C.; Newson, Lisa; Marcus, Michael W.; Field, John K.; Robinson, Jude
Abstract : Objectives: Electronic cigarettes (e‐cigarettes) are promoted as smoking cessation tools, yet they remain unavailable from Stop Smoking Services in England; the debate over their safety and efficacy is ongoing. This study was designed to explore perceptions and reasons for use or non‐use of electronic cigarettes as smoking cessation tools, among individuals engaged in Stop Smoking Services. Methods: Semi‐structured telephone interviews were undertaken with twenty participants engaged in Stop Smoking Services in the north‐west of England. Participants comprised of both individuals who had tried e‐cigarettes ( n  =   6) and those who had not ( n  =   14). Interviews were digitally recorded and transcribed verbatim. The transcripts were subject to thematic analysis, which explored participants' beliefs and experiences of e‐cigarettes. Results: A thematic analysis of transcripts suggested that the following three superordinate themes were prominent: (1) self‐efficacy and beliefs in e‐cigarettes; (2) e‐cigarettes as a smoking cessation aid; and (3) cues for e‐cigarette use. Participants, particularly never users, were especially concerned regarding e‐cigarette efficacy and safety. Overall, participants largely expressed uncertainty regarding e‐cigarette safety and efficacy, with some evidence of misunderstanding. Conclusions: Evidence of uncertainty and misunderstanding regarding information on e‐cigarettes highlights the importance of providing smokers with concise, up‐to‐date information regarding e‐cigarettes, enabling smokers to make informed treatment decisions. Furthermore, identification of potential predictors of e‐cigarette use can be used to inform Stop Smoking Services provision and future research. Statement of contribution What is already known on this subject? Research suggests that e‐cigarettes may help smokers quit smoking, but further studies are needed. Electronic cigarette use in Stop Smoking Services has increased substantially in recent years, although e‐cigarettes are currently not regulated. There is debate within the academic community regarding e‐cigarette efficacy and safety. What does this study add? Service users interviewed in the current study felt uncertain regarding e‐cigarette efficacy and safety. E‐cigarette ever users viewed e‐cigarettes as effective and safe, more often than never users. Accurate and up‐to‐date education will enable service users to make informed treatment decisions.